Application of the Teams Game Tournament Model to Increase Biology Learning Activeness - Dwi Indah Lestari; Dwi Oetomo; Puguh Karyanto (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2023)
Teachers and students need an adjustment period to adapt from distance learning to face-to-face learning. This condition raises problems in the teaching and learning process. The research used classroom action research as a research design for implementing the TGT cooperative learning method to increase the activeness of class X students in Biology learning. The learning activeness of Class X students in biology subject categorized as low. To improve it, the researcher utilized a fun method such as TGT. The research participants were sixteen class X MIPA SMA Islam 1 Surakarta students. Data collection techniques of the research used observation, questionnaires, and tests. Comparative descriptive statistics were used to examine the quantitative data, while critical analysis was used to analyze the qualitative data. The results of the data analysis presented that students' learning activeness increased to the high category (≥ 75%) with details of 75% visual activity, 76% verbal activity, 83% listening activity, 76% writing activity, 96% motoric activity, 89% mental activity, and 86% vigorous activity. These results arise due to the active role of students in the syntax of games and matches. Nature card media generate students' interest in learning, because contain picture-cued of surrounding natural phenomena in the student environment. The card's questions were scaled to the student's cognitive capacity level and impacted the student's self-awareness to care about the environment. It can be concluded that contextual learning of the environment change with the TGT model can increase student learning activity, especially in Biology lessons.